Risk factors of aortic regurgitation progression in Chinese patients with Takayasu's arteritis: a prospective cohort study - Yujiao Wang; Lili Ma; Ying Sun; Wensu Yu; Sifan Wu; Huiyong Chen; Xiaomin Dai; Lingying Ma; Lindi Jiang (SAGE Publishing, 2022)
Objective: To elucidate the 3-year follow-up outcomes and risk factors associated with aortic regurgitation progression in Takayasu's arteritis (TAK). Methods: This study was a prospective cohort study conducted among 77 patients with TAK at Zhongshan Hospital, Fudan University, China. All the participants were followed up and assessed with echocardiography for 3 years, and the baseline characteristics and dynamic changes in the aortic valve were recorded and investigated. A multivariable Cox model was used to explore the risk factors for aortic regurgitation progression. Results: The median onset age was 36.9 (26.0-44.4) years, and 57 patients (74.0%) were females. Fifty patients (64.9%) complained of aortic regurgitation, which was the most common valvular lesion at baseline. During the 3-year follow-up period, the progression of aortic regurgitation was observed in 29 (37.7%) patients with TAK. The progression group had higher baseline erythrocyte sedimentation rate (ESR; p  = 0.013) and interleukin (IL)-6 ( p  = 0.029) levels and lower early treatment remission rates ( p  = 0.024). According to the Cox model, the elevated baseline IL-6 level [>13 pg/ml, hazard ratio (HR) = 2.4, 95% confidence interval (CI) = 1.0-5.8, p  = 0.042] and absence of early treatment remission (HR = 3.3, 95% CI = 1.3-8.2, p  = 0.010) were the independent risk factors for aortic regurgitation deterioration. Conclusion: About one-third of patients with TAK experienced aortic regurgitation progression within 3 years from first admission. Elevated IL-6 levels at baseline and absence of early treatment remission were the two important risk factors for subsequent aortic regurgitation progression.